War allegory in Narayan Wagle's Palpasa Café - Jujar Singh, Hardev Kaur; Abu Jweid, Abdalhadi Nimer Abdalqader (Universiti Putra Malaysia Press, 2018)
This article examines the metafictional representations in Narayan Wagle's Palpasa Café (2008). The novel's metafictional elements depict the state of the Nepalese people during the Civil War. Wagle critiques the devastating consequences of the Civil War and how it affected the Nepali individuals' psyche. The study elucidates Wagle's use of metafiction as an indirect commentary on the political status quo. The study also uses allegory to explicate the metafictional elements in the novel in order to highlight Wagle's fictional critique. Allegory is elaborated in terms of paradox. Paradoxical allegory reveals the implicit metafictional authorial presence in the novel's narrative structure to accentuate the author's subjective voice. Such authorial presence is conveyed via insinuating self-reflexivity device which allows the author to intervene in his narrative fabric. The study mainly focuses on the authorial metafictional interference within the fictional text through paradoxical allegory. Both allegory and paradox have an interrelation with metafiction which unravels the author's relative perspective on the tragic consequences of the Nepalese Civil War.